All-Russian Scientific and Practical Conference with international participation Current issues of prevention infectious and non-infectious diseases: epidemiological, organizationa and hygienic aspects – October 25–27, 2023 - Article Editorial (Эпидемиология и вакцинопрофилактика, 2023)
.